2017
DOI: 10.1002/2017gl074476
|View full text |Cite
|
Sign up to set email alerts
|

Underlying causes of Eurasian midcontinental aridity in simulations of mid‐Holocene climate

Abstract: Climate model simulations uniformly show drier and warmer summers in the Eurasian midcontinent during the mid‐Holocene, which is not consistent with paleoenvironmental observations. The simulated climate results from a reduction in the zonal temperature gradient, which weakens westerly flow and reduces moisture flux and precipitation in the midcontinent. As a result, sensible heating is favored over evaporation and latent heating, resulting in substantial surface‐driven atmospheric warming. Thus, the discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 120 publications
(132 reference statements)
3
26
0
Order By: Relevance
“…These changes gave rise to a climate radically different from that of today; indeed the magnitude of the change in radiative forcing between LGM and pre-industrial climate is comparable to highemissions projections of climate change between now and the end of the 21st century (Braconnot et al, 2012). The LGM has been a focus for model evaluation in the Paleoclimate Modelling Intercomparison Project (PMIP) since its inception (Joussaume and Taylor, 1995;Braconnot et al, 2007Braconnot et al, , 2012. The LGM is one of the two "entry card" palaeoclimate simulations included in the current phase of the Coupled Model Intercomparison Project (CMIP6) (Kageyama et al, 2018).…”
Section: S F Cleator Et Al: Multivariable Lgm Palaeoclimate Reconsmentioning
confidence: 99%
“…These changes gave rise to a climate radically different from that of today; indeed the magnitude of the change in radiative forcing between LGM and pre-industrial climate is comparable to highemissions projections of climate change between now and the end of the 21st century (Braconnot et al, 2012). The LGM has been a focus for model evaluation in the Paleoclimate Modelling Intercomparison Project (PMIP) since its inception (Joussaume and Taylor, 1995;Braconnot et al, 2007Braconnot et al, , 2012. The LGM is one of the two "entry card" palaeoclimate simulations included in the current phase of the Coupled Model Intercomparison Project (CMIP6) (Kageyama et al, 2018).…”
Section: S F Cleator Et Al: Multivariable Lgm Palaeoclimate Reconsmentioning
confidence: 99%
“…Climate and climate variability are determined by the amount of incoming solar radiation, chemical composition and dynamics of the atmosphere, and surface characteristics of the earth [1][2][3]. The surface characteristics of the earth often affect the regional and local patterns of climate through the redistribution of energy [4][5][6]. As a unique underlying surface covering about 40% of terrestrial surface, deserts make a vital contribution to the global climate system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of previous generations of palaeoclimate simulations has shown that the large-scale thermodynamic responses seen in 21 st century and LGM climates, including enhanced land-sea temperature contrast, latitudinal amplification, and scaling of precipitation with temperature, are likely to be realistic (Izumi et al, 2013;Li et al, 2013;Lunt et al, 2013;Hill et al, 2014;Izumi et al, 2014;Harrison et al, 2015). However, evaluation against palaeodata shows that even when the sign of large-scale climate changes is correctly predicted, the patterns of change at a regional scale are often inaccurate and the magnitudes of change often underestimated (Brewer et al, 2007;Mauri et al, 2014;Perez Sanz et al, 2014;Bartlein et al, 2017). The current focus on understanding what causes mismatches between reconstructed and simulated climates is a primary motivation for developing benchmark data sets that represent regional climate changes comprehensively enough to allow a critical evaluation of model deficiencies.…”
Section: Introductionmentioning
confidence: 99%